Effectiveness of Augmented Reality-Assisted Problem-Based Learning Model on Science Learning Outcomes - Muhamad Azril Gibran; Novi Setyasto (Postgraduate, University of Mataram, 2025)
The implementation of learning models that are not in accordance with the provisions of the Minister of Education, Culture, Research and Technology Regulation Number 16 of 2022 concerning Process Standards, as well as not maximizing the integration of technology media into learning, has an impact on low student learning outcomes. This study examines the effectiveness of the Problem-Based Learning model assisted by Augmented Reality compared to the Problem-Based Learning model assisted by images on the learning outcomes of Class V Science at SD Negeri Gugus Budi Utomo. This type of research is experimental research with a Quasi-Experimental Design research design in the form of Non-equivalent Control Group Design. Data analysis techniques included initial data analysis with normality and homogeneity tests and final data analysis with independent sample t-test and N-Gain tests. The hypothetical results of the independent sample t-test obtained a Sig. (2-tailed) value of 0.032 and 0.034 (sig. <0.05), so H0 is rejected and Ha is accepted. This is reinforced by the results of the N-Gain test of the experimental class of 0.430 (moderate) and the control class of -.004 (low). It can be concluded that the Problem-Based Learning model assisted by Augmented Reality is more effective than the Problem-Based Learning model assisted by images on the learning outcomes of Science Class V of SD Negeri Gugus Budi Utomo.